PENGARUH KONSENTRASI KEPEMILIKAN, KEPEMILIKAN INSTITUSIONA, PROPORSI DEWAN KOMISARIS INDEPENDEN, DAN FREKUENSI RAPAT KOMITE AUDIT TERHADAP PRAKTIK MANAJEMEN LABA - Belinda Yuna Amalia; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
The aims of this study is to examine the effect of ownership concentration, proportion of independent board, institutional ownership, frequency of committee audit meetings, as an independent variable, dan size and leverage as a control variable and earnings management practices as a dependent variable.The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2011-2015. The method used is purposive sampling with certain criteria. After going through the sampling and processing of data obtained final sample decent observed that 245 companies. This study uses multiple regression analysis to test hypothesis of the study.The results of this study showed that frequency meetings committee audit, and size have significant negative influence to earning management, while ownership concentration,institutional ownership,leverage, also proportion of independent board doesn not significantly affect of earnings managemen.